Identification and characterization of the polyketide synthase involved in ochratoxin A biosynthesis in Aspergillus carbonarius - Gallo, Antonia; Knox, Benjamin P.; Bruno, Kenneth S.; Solfrizzo, Michele; Baker, Scott E.; Perrone, Giancarlo (International journal of food microbiology, 2014)
Ochratoxin A (OTA) is a potent mycotoxin produced by Aspergillus and Penicillium species and is a common contaminant of a wide variety of food commodities, with Aspergillus carbonarius being the main producer of OTA contamination in grapes and wine. The molecular structure of OTA comprises a dihydroisocoumarin ring linked to phenylalanine and, as shown in different producing fungal species, a polyketide synthase (PKS) is a component of the OTA biosynthetic pathway. Similar to observations in other filamentous ascomycetes, the genome sequence of A. carbonarius contains a large number of genes predicted to encode PKSs. In this work a pks gene identified within the putative OTA cluster of A. carbonarius, designated as AcOTApks, was inactivated and the resulting mutant strain was unable to produce OTA, confirming the role of AcOTApks in this biosynthetic pathway. AcOTApks protein is characteristic of the highly reduced (HR)-PKS family, and also contains a putative methyltransferase domain likely responsible for the addition of the methyl group to the OTA polyketide structure. AcOTApks is different from the ACpks protein that we previously described in A. carbonarius, which showed an expression profile compatible with OTA production. We performed phylogenetic analyses of the β-ketosynthase and acyl-transferase domains of the OTA PKSs that had been identified and characterized in different OTA producing fungal species. The phylogenetic results were similar for both domains analyzed and showed that OTA PKS of A. carbonarius, Aspergillus niger and Aspergillus ochraceus clustered in a monophyletic group with 100% bootstrap support suggesting a common origin, while the other OTA PKSs analyzed were phylogenetically distant. A quantitative RT-PCR assay monitored AcOTApks expression during fungal growth and concomitant production of OTA by A. carbonarius in synthetic grape medium. A clear correlation between the expression profile of AcOTApks and kinetics of OTA production was observed, with AcOTApks reaching its maximum level of transcription before OTA accumulation in mycelium reached its highest level, confirming the fact that gene transcription always precedes phenotypic production. •The pks gene identified in the OTA cluster of Aspergillus carbonarius was inactivated.•AcOTApks protein is responsible of OTA biosynthesis in Aspergillus carbonarius.•Phylogenetic analyses of KS and AT domains of fungal OTA PKSs were performed.•A qRT-PCR assay was developed to monitor the expression of AcOTApks.